Start your own lawn care or landscaping business : your step-by-step guide to success - Linsenmann, Ciree ([Irvine, Calif.] : Entrepreneur Press, 2011)
"A start up guide with ideas and various suggestions on starting your own lawncare and landscaping business"--
Fakulti Keusahawanan dan Perniagaan.
Refer to invoice YPJ-1 (00030188/5243)
Includes bibliographical references and index.
Keywords: Landscaping industry -- Management; Lawn care industry -- Management; New business enterprises; Small business